THE EFFECT OF ADENOTONSILLECTOMY ON THE QUALITY OF LIFE AMONG CHILDREN TWO TO THIRTEEN YEARS OF AGE - Zmnako, Sherko Saeed Fathulla; Chalabi, Yusuf Ibrahim; Said, Said Mustafa; Ameen, Huner Mohamed Hama; Krim, Rekawt Hama Rashid; Mohammed, Mohammed Subhan (Journal of Sulaimani Medical College, 2017)
Background The tonsils and adenoid enlargement are the most common cause of respiratory tract obstruction in children and cause obstructive sleep apnea and snoring. These children may present with recurrent upper respiratory tract infection with frequent antibiotic uses. Parents may worry about some alteration in children’s behavior and development which are caused by adenotonsillar enlargement. Objectives To evaluate the quality of life of children with adenotonsillar enlargement, recurrent and chronic tonsillitis before and after adenotonsillectomy. Patients and Methods A prospective observational study done. Data collected from (January 2015 to end of July, 2015). Parents of 118 children who underwent adenotonsillectomy in (ENT, Head and Neck Surgery – Sulaimani Teaching Center) were interviewed before the operation and 6 months after the operation, by using the questionnaire about quality of life, physical problems, sleeping problems, speech and swallowing problems, emotional discomfort, limitation of activities and parents’ concerns; each of them scored from zero to six. Results The score obtained by the questionnaire after adenotonsillectomy significantlyreduced as compared to the score obtained before the operation. Symptoms which have the highest scores before the operation are nasal obstruction and snoring. There was a decrease in the number of upper respiratory tract infections after the adenotonsillectomy. There was a significant decrease in the use of antibiotics after adenotonsillectomy. Conclusion We conclude that the quality of life of these children improved after adenotonsillectomy, especially the physical problems and sleep problems, the number of upper respiratory tract infections decreased and the decrease in the use of antibiotics, but children who have had symptoms of rhinitis had less improvement in their quality of life compared to the children who didn’t have these symptoms.
Keywords: Adenoid; Tonsils; Quality of life